Applying Model‐Based Systems Engineering Methods to a Novel Shared Systems Simulation Methodology. Issue 1 (26th September 2022) - Ross, Jeremy; Vinarcik, Michael; Caron, Christopher; Craft, Christopher; Pien, Stephen; Prajapati, Ashishkumar
Abstract: The need to develop increasingly complex, integrated systems and multi‐domain systems‐of‐systems is initiating a transformation within the discipline of systems engineering. The critical trends of increasing interconnectivity, compressed development times, growing cybersecurity concerns, and a rapidly changing workforce are driving current systems engineering practices into obsolescence. Model‐Based Systems Engineering (MBSE) is a formalized approach to systems engineering that uses models as an integral component of a system's technical definition with the objective of enhancing communication through rigor and precision and managing system complexity. This paper discusses the application of MBSE methods to the definition of a shared systems architecture and the development of novel methodologies for extending the model‐based approach from the system definition space into the system simulation and analysis domain. Approaches for interface management of design properties between a model‐based architecture and system simulation will be reviewed, with the effectiveness of each approach discussed.